Financing infrastructure development: time to unshackle the bonds?. Issue 3 (4th April 2016) - Hutchison, Norman; Squires, Graham; Adair, Alastair; Berry, Jim; Lo, Daniel; McGreal, Stanley; Organ, Sam
Abstract : Purpose: – The purpose of this paper is to consider the merits of using projects bonds to finance infrastructure investment projects and considers the pricing of such bonds and the level of risk premium demanded by the market. Design/methodology/approach: – The research used a mix of qualitative and quantitative methods with desk-based study and interviews. Interviews were held with policy makers, local authority staff, planners, developers, investors, fund managers and academics. Infrastructure bond data were obtained from the Bloomberg database on all project bonds issued in four Asian countries – Malaysia, China, Taiwan and India – over the period 2003-2014. Findings: – The analysis indicates investor appetite for project bonds and suggests that a risk premium of between 150 and 300 basis points over the comparable government bond is appropriate depending on the sector and the degree of government involvement in underwriting the issue. Practical implications: – The paper argues that the introduction of project bonds would be an important innovation, assisting the financing of infrastructure investment at a time when bank lending is likely to remain fragile. The current conditions in the sovereign debt market, where strong demand has forced down yields, has opened up the opportunity to introduce project bonds offering a higher yield to satisfy institutional investment demand for long term fixed income products. Originality/value: – The originality of this paper stems from the analysis of the merits of using projects bonds to finance infrastructure investment projects, the pricing of such bonds and the level of risk premium demanded by the market.